(untitled) (Altre Modernità, 2018)
The study investigates dialogic strategies in selected corporate communication of the biotech giants Monsanto and Bayer. Both companies have had to repeatedly face criticism on the part of activists and biotech-averse consumers. In order to win consumer trust and gain social legitimation, the companies have put considerable effort into building forms of stakeholder dialogue, resorting, to this end, to computer mediated communication as the preferred means of interaction. Monsanto’s and Bayer’s commitment to engage dialogically with their audiences provides a set of ideal materials for testing if and to what extent new technological affordances are used by companies in the service of stakeholder dialogue on potentially controversial themes. The study analyzes the communicative coordinates and rhetorical organization of communication in two distinct sets of documents – Monsanto’s dedicated “Conversation” website section, and Bayer’s “Transparency Initiative” introductory video. The methodological toolkit used for the analysis is discourse-analytical in focus and draws on tools developed within Systemic Functional linguistics for the analysis of interpersonal resources, and on pragmadialectics for the exploration of the argumentative and rhetorical strategies deployed in the service of persuasion in respect of corporate goodwill/commitment in the face potentially oppositional discourse. The analysis highlights the challenges posed by dialogic overture on controversial issues, and suggests that a tension exists between transparency/openness and discursive foreclosure/gatekeeping which is very hard for companies to negotiate.